Analisis Nilai Perusahaan Pada Perusahaan Sub Sektor Nondurable Household Products Yang Terdaftar di Bursa Efek Indonesia - Meylani, Meylani; Amrullah Suwaidi, Rahman (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2025)
This study aims to examine the effect of profitability, activity ratio, and company growth on company value in the Nondurable Household Products sub-sector listed on the Indonesia Stock Exchange for the 2017–2023 period. Company value is a major concern because it reflects investor perceptions of company performance, and is measured using Price to Book Value (PBV). The independent variables in this study are profitability as measured by Return on Equity (ROE), activity ratio as measured by Total Assets Turnover (TATO), and company growth as measured by Total Assets Growth (TAG). The sampling method used is purposive sampling, with a sample size of 5 companies. The data analysis technique used is multiple linear regression analysis with the help of SPSS version 25 software. The results of the study indicate that partially profitability (ROE) contributes to firm value. However, the activity ratio (TATO) and firm growth (TAG) contribute to firm value.